ChemInform Abstract: Nanowire Chemical/Biological Sensors: Status and a Roadmap for the Future. Issue 11 (February 2016) - Fennell, John F. Jr.; Liu, Sophie F.; Azzarelli, Joseph M.; Weis, Jonathan G.; Rochat, Sebastien; Mirica, Katherine A.; Ravnsbaek, Jens B.; Swager, Timothy M.
Abstract: Review: 251 refs.